The black hole candidate MAXI J1659-152 in and towards quiescence in X-ray and radio - Jonker, P.; Miller-Jones, James; Homan, J.; Tomsick, J.; Fender, R.; Kaaret, P.; Markoff, S.; Gallo, E. (Wiley-Blackwell Publishing Ltd., 2012)
In this paper we report on Expanded Very Large Array radio and Chandra and Swift X-ray observations of the outburst decay of the transient black hole candidate MAXI J1659-152 in 2011. We discuss the distance to the source taking the high inclination into account and conclude that the source distance is probably 6 ± 2 kpc. The lowest observed flux corresponds to a luminosity of 2x10^31 (d/6kpc)^2 erg s-1. This, together with the orbital period of 2.4 h reported in the literature, suggests that the quiescent X-ray luminosity is higher than predicted on the basis of the orbital period-quiescent X-ray luminosity relationship. It is more in line with that expected for a neutron star, although the outburst spectral and timing properties reported in the literature strongly suggest that MAXI J1659-152 harbours a black hole. This conclusion is subject to confirmation of the lowest observed flux as the quiescent flux. The relation between the accretion and ejection mechanisms can be studied using the observed correlation between the radio and X-ray luminosities as these evolve over an outburst. We determine the behaviour of MAXI J1659-152 in the radio-X-ray diagram at low X-ray luminosities using the observations reported in this paper and at high X-ray luminosities using values reported in the literature. At high X-ray luminosities, the source lies closer to the sources that follow a correlation index steeper than 0.6-0.7. However, when compared to other sources that follow a steeper correlation index, the X-ray luminosity in MAXI J1659-152 is also lower. The latter can potentially be explained by the high inclination of MAXI J1659-152 if the X-ray emission comes from close to the source and the radio emission is originating in a more extended region.However, it is probable that the source was not in the canonical low-hard state during these radio observations and this may affect the behaviour of the source as well. At intermediate X-ray luminosities, the source makes the transition from the radio underluminous sources in the direction of the relation traced by the 'standard' correlation similar to what has been reported for H 1743-322 in the literature. However, MAXI J1659-152 remains underluminous with respect to this 'standard' correlation.